Long-term neurocognitive outcomes of SARS-CoV-2 infection in a hamster model - Ruiz-Casas, Carla; Tarrés-Freixas, Ferran; Roca, Núria; Pérez, Mònica; Cantero, Guillermo; Martín, Laura; Olvera, Alex; Ruiz-Riol, Marta; Brander, Christian; Usai, Carla; Vergara-Alert, Júlia; Segalés, Joaquim (Frontiers in Microbiology, 2025)
IntroductionPost-COVID-19 condition (PCC) is a long-lasting, multisystemic syndrome affecting approximately 30% of individuals after acute COVID-19, with neurological symptoms among the most prevalent and debilitating. Despite its substantial global health impact, the biological mechanisms underlying PCC remain poorly understood, underscoring the need for validated animal models.MethodsTo address this, we conducted a longitudinal study using the golden Syrian hamster model, integrating virological, immunological, histopathological, and behavioral analyses from the acute phase to 60 days post-inoculation.ResultsOur results showed persistent viral RNA, prolonged immune dysregulation, and behavioral changes that mirrored key features of human PCC.DiscussionAlthough fully reproducing PCC in animal models is inherently challenging due to its complex and heterogeneous presentation in humans, the use of complementary models with distinct phenotypes is essential for elucidating its pathophysiology. These results aim to contribute valuable insights into the biological basis of PCC and support the development of targeted preventative and therapeutic strategies.